Han a short film : the emotional impact of production design - Liew, Julie Heather Shan Ting (2016)
Seamless production design allows viewers to be fully invested in the characters and narrative, and that was exactly what I hoped to achieve for Han (2016) and create an authentic and thoughtful backdrop for the dramatic narrative.